58.0k views
4 votes
Rewrite the expression in the form y^n

Rewrite the expression in the form y^n-example-1

2 Answers

5 votes

Answer:


y^6

Explanation:

The applicable rules of exponents are ...


y^ay^b=y^(a+b)\\\\(1)/(y^(-a))=y^a

Using these rules, you can write the expression as ...


(y^(-7))/(y^(-13))=y^(-7-(-13))=y^6

User Mawburn
by
5.7k points
5 votes

Answer:


$ y^6 $

Explanation:


$ (a^b)/(a^c) = a^(b - c) $

Using this rule we have:


$ (y^(-7))/(y^(-13))  = y^(-7 -(-13)) = y^6$

User User Unknown
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.